Manejo agronómico del cultivo de arazá (Eugenia stipitata) en el Ecuador. - Morales Mora, Lady Elizabeth (2024)
Arazá (Eugenia stipitata), also known as Brazilian guava or Amazonian guava, is a tropical fruit with a sweet and sour flavor and a distinctive aroma. Its cultivation extends throughout several South American countries, including Ecuador, where agronomic practices are implemented to improve its yield and quality, making it a promising producto in both local and international markerts. With the objective of determining agronomic practices in the cultivation of arazá (E. stipitata) in Ecuador. The methodology of this research was base don the collection of updated information, such as scientific articles, websites, books and virtual libraries. The results highlight the importance of soil management, the selection of resistant varieties and the implementation of efficient irrigation systems to increase the productivity of arazá cultivation. The production of arazá in Ecuador takes place mainly in warm and humid areas, with the Coast, Sierra and Amazon regions being the main producto areas of this fruit. In conclusion, agronomic activities such as pruning, irrigation, fertilization, among other agricultural practices are essential to impromove the productivity and quality of the araza crop. The arazá shows a notable adaptability to different climates in Ecuador, promoting its cultivation in various regions of the coast (Esmeraldas, Manabí, Santo Domingo de los Tsáchilas, Los Ríos and Guayas), Sierra (Pichincha) and Amazonia (Sucumbíos, Orellana, Napo, Pastaza and Morona Santiago) and contributing to the economic development of the country.